2021
DOI: 10.33369/pendipa.6.1.57-63
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Mitigasi Bencana Banjir di Kabupaten Pidie Jaya Provinsi Aceh untuk Mendukung Keamanan Nasional

Abstract: Flood Disaster Mitigation Efforts in Pidie Jaya District, Aceh Province to Support National Security].This study was conducted to analyze flood disaster mitigation efforts in Pidie Jaya District to support national security. This research used a qualitative method and descriptive analysis. The data used in this research were primary and secondary data. Primary data was obtained through interviews conducted online using the zoom meeting application on March 22-25, 2021 involving several agencies in Pidie Jaya D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
0
1
Order By: Relevance
“…Pelatihan mitigasi bencana banjir ini membuka wawasasan, pengetahuan, dan kemampuan masyarakat dalam penanganan bencana banjir. Sesuai dengan hasil penelitian ini upaya-upaya mitigasi untuk bencana banjir seperti, melakukan koordinasi dengan lintas sektor terkait, melakukan identifikasi kawasan rawan bencana, melakukan sosialisasi dan memberikan edukasi tentang penanggulangan bencana (Kharimah, et al, 2022). Edukasi melalui pelatihan kepada masyarakat tentang mitigasi bencana banjir selalu di update sehingga masyarakat tidak bertolak belakang dengan pemerintah dalam mitigasi bencana banjir (Widyanto, 2018).…”
Section: B Pembahasanunclassified
“…Pelatihan mitigasi bencana banjir ini membuka wawasasan, pengetahuan, dan kemampuan masyarakat dalam penanganan bencana banjir. Sesuai dengan hasil penelitian ini upaya-upaya mitigasi untuk bencana banjir seperti, melakukan koordinasi dengan lintas sektor terkait, melakukan identifikasi kawasan rawan bencana, melakukan sosialisasi dan memberikan edukasi tentang penanggulangan bencana (Kharimah, et al, 2022). Edukasi melalui pelatihan kepada masyarakat tentang mitigasi bencana banjir selalu di update sehingga masyarakat tidak bertolak belakang dengan pemerintah dalam mitigasi bencana banjir (Widyanto, 2018).…”
Section: B Pembahasanunclassified
“…Beberapa kota yang mengalami banjir tahunan seperti Jakarta, Semarang, Surabaya dan Bandung. Sedangkan didaerah pedesaan sering terjadi namun luput dari pemberitaan (Kharimah et al, 2021). Banjir di daerah pedesaan umumnya disebabkan oleh gundulnya hutan sehingga debit air sungai meluap atau bisa disebut banjir bandang.…”
Section: Pendahuluanunclassified
“…, storage and others (Afrian, 2020). The second study conducted by Islamia Kharimah (2021), which investigated disaster reduction efforts in Pidie Jaya District, Aceh Province, found that with the help of cross-sectoral and government coordination, identifying disaster-prone areas and strengthening disaster management structures. Furthermore, the third researcher from Anastasia Bongi et al If the level of disaster risk is high, disaster reduction is in the form of policies included in the reduction plan, the average risk level, then what is done is to focus on additions and improvements, and those that have a low level of risk.…”
Section: Introductionmentioning
confidence: 99%